GREAT POWER RIVALRY FROM THE PERSPECTIVES OF REALISM AND LIBERALISM - Xudoyberdiyev Otabek Zafar o'g'li (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
This article analyzes the phenomenon of great power rivalry through the lenses of two dominant theories in international relations: realism and liberalism. It compares how each theory explains the causes, dynamics, and consequences of competition among powerful states. While realism emphasizes power politics, national interests, and the inevitability of conflict in an anarchic international system, liberalism highlights the role of international institutions, economic interdependence, and democratic values in mitigating rivalry. By applying both theoretical frameworks to contemporary examples—such as U.S.–China relations and NATO–Russia tensions—the paper aims to provide a balanced understanding of how theoretical paradigms shape the interpretation of global strategic competition.